Penggunaan Media Video Animasi Interaktif Guna Meningkatkan Minat Belajar Siswa SD - Tri Susanti, Irma; Nofita Sari, Ema; Merkuri, Andriyani; Wahyudi, Apri (UNIB Press, 2024)
The aim of this research is to identify the benefits of using interactive animated video media to enhance elementary school students' interest in learning. The method employed in this study is a literature review, examining various relevant scientific journals. The research findings indicate that the use of interactive animated video media can provide significant benefits in the learning process. These benefits include delivering engaging material, making learning enjoyable, and increasing students' interest in learning.